Comparative genomic analysis revealed that dietary habits affected the adaptation of Bifidobacterium bifidum to the intestinal tract in different geographic populations - Min Li; Jie Yu; Weicheng Li; Qiong Wu; Jiaqi Sun; Zhihong Sun (Food Science and Human Wellness)
Recent research on the genome of Bifidobacterium bifidum has mainly focused on the isolation sources (intestinal tract niche) recently, but reports on the isolation region are limited. This study analyzed the differences in the genome of B. bifidum isolated from different geographical populations by comparative genomic analysis. Results at the genome level indicated that the GC content of American isolates was significantly higher than that of Chinese and Russian isolates. The phylogenetic tree, based on 919 core genes showed that B. bifidum might be related to the geographical characteristics of isolation region. Furthermore, functional annotation analysis demonstrated that copy numbers of carbohydrate-active enzymes (CAZys) involved in the degradation of polysaccharide from plant and host sources in B. bifidum were high, and 18 CAZys showed significant differences across different geographical populations, indicating that B. bifidum had adapted to the human intestinal environment, especially in the groups with diets rich in fiber. Dietary habits were one of the main reasons for the differences of B. bifidum across different geographical populations. Additionally, B. bifidum exhibited high diversity, evident in glycoside hydrolases, the CRISPR-Cas system, and prophages. This study provides a genetic basis for further research and development of B. bifidum.